HIGHER EDUCATION FOR NATIONAL MINORITIES IN THE PRC - J. P. Pomelova (Вестник Мининского университета, 2017)
This paper examines China's educational policies in terms of historical, political and ideological contexts. Practical issues of organization and implementation of educational policy in relation to higher education for ethnic minorities are discussed.